Modeling avian eggshell microstructure to predict ontogenetic age and reveal patterns of human-avifauna interaction. (September 2021) - Douglass, Kristina; Bulathsinhala, Priyangi; Feo, Teresa J.; Tighe, Tim; Whittaker, Scott; Brand, Zanell; James, Helen; Rick, Torben
Abstract: Archaeological eggshell is a commonly recorded, yet underutilized material for understanding human-environment interaction in the past. In addition to the use of archaeological eggshell as a paleoenvironmental proxy, archaeologists have innovated important new approaches to the study of archaeological avian eggshell, including the application of scanning electron microscopy (SEM) for the characterization of eggshell microstructures. These studies have demonstrated the importance of eggshell for understanding how ancient communities exploited and interacted with avifauna. In this paper, we build on these methodological advances by testing new approaches to image avian eggshell and characterizing complex eggshell surface microstructures. We demonstrate the utility of capturing high-resolution 3-dimensional (3D) eggshell surfaces using advanced imaging modalities (optical profilometry, scanning electron microscopy, digital microscopy, computed tomography), to model changes in eggshell microstructures that are correlated with ontogeny. Using the Common Ostrich ( Struthio camelus ) as our model system, we introduce a statistical modeling approach to predict the ontogenetic age of ratite eggshell using roughness measurements of 3D features. Successful prediction of ontogenetic age has great potential to reveal archaeological patterns of human exploitation of avian eggs. These findings further illustrate the importance of archaeological eggshell for investigating human-environment interactions, emphasizing the need for archaeologists to use field methods (hand/trowel excavation and fine mesh screen) that facilitate eggshell recovery. Highlights: Eggshell is underutilized and can clarify past human-avifauna interaction. We demonstrate the utility of capturing high-resolution 3D surfaces of eggshell. We characterize changes in eggshell microstructure linked to embryonic development. We developed statistical models to predict eggshell ontogenetic age. Assessment of eggshell ontogenetic age can be used to infer human exploitation.